Pengaruh Budaya Organisasi Dan Kepemimpinan Terhadap Kinerja Karyawan Pada PT. Pratama Abadi Industri Divisi Manufakturing - Noviana Ramadan Sapriti; Nurul Ilham (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study was to determine the influence of organizational culture and leadership on employee performance at PT Pratama Abadi Industri Manufacturing Division. The method used is quantitative. The sampling technique used saturated sampling, namely 80 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test. The results of this study are organizational culture has a significant effect on employee performance with a determination coefficient value of 55.6% and the hypothesis test obtained t count> t table or (9.277> 1.990). Leadership has a significant effect on employee performance with a determination coefficient value of 69.6% and the hypothesis test obtained t count> t table or (12.478> 1.990). Organizational culture and leadership simultaneously have a significant effect on employee performance with a regression equation Y = 8.151 + 0.175X1 + 0.632X2. The determination coefficient value is 70.5% while the remaining 41.4% is influenced by other factors. The hypothesis test yielded a calculated F value > F table, or (79.917 > 3.12).